Multi-omics unveils strain-specific neuroactive metabolite production linked to inflammation modulation by Bacteroides and their extracellular vesicles - Basit Yousuf; Walid Mottawea; Galal Ali Esmail; Nazila Nazemof; Nour Elhouda Bouhlel; Emmanuel Njoku; Yingxi Li; Xu Zhang; Zoran Minic; Riadh Hammami (Current Research in Microbial Sciences)
Bacteroides species are key members of the human gut microbiome and play crucial roles in gut ecology, metabolism, and host-microbe interactions. This study investigated the strain-specific production of neuroactive metabolites by 18 Bacteroidetes (12 Bacteroides, 4 Phocaeicola, and 2 Parabacteroides) using multi-omics approaches. Genomic analysis revealed a significant potential for producing GABA, tryptophan, tyrosine, and histidine metabolism-linked neuroactive compounds. Using untargeted and targeted metabolomics, we identified key neurotransmitter-related or precursor metabolites, including GABA, l-tryptophan, 5-HTP, normelatonin, kynurenic acid, l-tyrosine, and norepinephrine, in a strain- and media-specific manner, with GABA (1–2 mM) being the most abundant. Additionally, extracellular vesicles (EVs) produced by Bacteroides harbor multiple neuroactive metabolites, mainly GABA, and related key enzymes. We used CRISPR/Cas12a-based gene engineering to create a knockout mutant lacking the glutamate decarboxylase gene (gadB) to demonstrate the specific contribution of Bacteroides finegoldii-derived GABA in modulating intestinal homeostasis. Cell-free supernatants from wild-type (WT, GABA+) and ΔgadB (GABA-) provided GABA-independent reinforcement of epithelial membrane integrity in LPS-treated Caco-2/HT29-MTX co-cultures. EVs from WT and ΔgadB attenuated inflammatory immune response of LPS-treated RAW264.7 macrophages, with reduced pro-inflammatory cytokines (IL-1β and IL-6), downregulation of TNF-α, and upregulation of IL-10 and TGF-β. GABA production by B. finegoldii had a limited impact on gut barrier integrity but a significant role in modulating inflammation. This study is the first to demonstrate the presence of a myriad of neuroactive metabolites produced by Bacteroides species in a strain- and media-specific manner in supernatant and EVs, with GABA being the most dominant metabolite and influencing immune responses.